Four asymmetric bis-branched triphenylamine derivatives with charge transfer from one branch to the other: Two-photon emissions and bio-imaging applications. (March 2017) - Gan, Xiaoping; Ge, Xinping; Zhai, Chengkai; Zheng, Jun; Tang, Xuguang; Yang, Yanchao; Tian, Yupeng; Zhang, Xuanjun; Zhou, Hongping
Abstract: Four asymmetric bis-branched triphenylamine-cored compounds with different electron-withdrawing groups have been synthesized and their optical properties have been systematically investigated. The two-photon absorption cross-section ( σ 2PA ) values were measured by two-photon excited fluorescence which revealed that the four compounds possessed large σ 2PA values from 2011 to 4173 GM in the near-infrared region. Theoretical calculations revealed that the compounds were all provided with interesting intramolecular charge transfer generated from one branch to the other which contributed to the large σ 2PA values. Cytotoxicity tests indicated that all these compounds had good biocompatibility for living cells, both one- and two-photon fluorescence microscopy studies showed the potential application of the four new compounds in cell imaging due to the large σ 2PA and appropriate biocompatibility. Graphical abstract: Highlights: Four asymmetric bis-branched triphenylamine derivatives were easily synthesized. The branched triphenylmines possessed large two-photon cross-sections and low biotoxicity. The intramolecular charge transfer from one branch to another plays an important role. The branched triphenylamines were successfully applied in one- and two-photon fluorescence bio-imaging.